2012
DOI: 10.4314/ejesm.v4i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Composting Process and Quality of Compost from Coffee By-Products (Coffee Husk & Pulp)

Abstract: Coffee pulp and husk are the main by-products generated by the coffee processing station and are disposed into arable land and surface water. Due to the contribution of these by-products to environmental pollution, environmentally friendly disposal methods are necessary. Therefore, composting as environmental friendly option for utilization of coffee by-products is important. The objectives of the study were to assess the properties of coffee by-products compost and analyzing changes in physico-chemical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
1
14
1
1
Order By: Relevance
“…The variation in nutrient content within the same post-harvest processing must be taking into account, but mainly when they are from different processing (Figure 3). Composting is also a good option for husk use [125,126].…”
Section: Coffeementioning
confidence: 99%
“…The variation in nutrient content within the same post-harvest processing must be taking into account, but mainly when they are from different processing (Figure 3). Composting is also a good option for husk use [125,126].…”
Section: Coffeementioning
confidence: 99%
“…In support to this result Varma [26] reported, leaching of nutrients including N, P and K from compost pile and composting drum and the leachate loss from drum composting method was the least compared to pile composing methods. On the other hand it could be due to decomposition state of the compost as a result of the different methods, since highly decomposed and stabilized compost contains high amount of potassium [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent case studies (Franca and Oliveira 2009;Kassa et al 2011;De Rezende et al 2012;Shemekite et al 2014;Degefe et al 2016) reported composting of coffee husk with cow dung, fruits/vegetables, effective microorganisms and Khat (Catha edulis). However, no research was carried out to investigate the composting and co-composting of coffee husk and pulp with source-separated municipal solid waste including the leaves of false banana (Ensete ventricosum), fruits, vegetables, khat/Catha edulis and soft dry wood at different proportions.…”
Section: Introductionmentioning
confidence: 99%